CD11c+ B Cells Are Mainly Memory Cells, Precursors of Antibody Secreting Cells in Healthy Donors - Golinski, Marie-Laure; Demeules, Mélanie; Derambure, Céline; Riou, Gaetan; Maho-Vaillant, Maud; Boyer, Olivier; Joly, Pascal; Calbo, Sébastien (Frontiers in Immunology, 2020)
CD11c+ B cells have been reported to be increased in autoimmune diseases, but they are detected in the blood of healthy individuals as well. We aimed to characterize CD11c+ B cells from healthy donors by flow cytometry, microarray analysis and in vitro functional assays. Here we report that CD11c+ B cells are a distinct subpopulation of B cells, enriched in the memory sub-population even if their phenotype is heterogeneous, with overexpression of genes involved in B cell activation and differentiation as well as in antigen presentation. Upon activation, CD11c+ B cells can differentiate into antibody secreting cells, and CD11c could be up-regulated in CD11c- B cells by B cell receptor activation. Finally, we show that patients with pemphigus, an autoimmune disease mediated by B cells, have a decreased frequency of CD11c+ B cell after treatment, relative to baseline. Our findings show that CD11c+ B cells are mainly memory B cells prone to differentiate into antibody secreting cells that accumulate with age, independently of gender.